Confirmation of the Dominant Defect Mechanism in Amorphous In–Zn–O Through the Application of In Situ Brouwer Analysis. Issue 7 (8th April 2015) - Moffitt, Stephanie L.; Adler, Alexander U.; Gennett, Thomas; Ginley, David S.; Perkins, John D.; Mason, Thomas O.; Zhou, X.‐D.
<x xml:space="preserve">Abstract</x> The dominant point defect mechanism of amorphous (a‐) indium zinc oxide (IZO) was probed through in situ electrical characterization of sputtered a‐IZO thin films in response to changes in oxygen partial pressure (pO<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1n9xfv29" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives>) at 300<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1n9xfv6h" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />∘</alternatives>C. The results yielded a power law dependence of conductivity (σ) versus pO<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1n9xfv5z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives> of ∼−1/6. This experimental method, known as Brouwer analysis, confirms doubly‐charged oxygen vacancies as the dominant defect species in a‐IZO. The success of this study suggests that Brouwer analysis is a viable method for studying the defect mechanisms of amorphous oxides.